2008
DOI: 10.1111/j.1096-3642.2007.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic signals, species diagnosis, and species concepts: the case of a new cryptic species of Leptodactylus (Amphibia, Anura, Leptodactylidae) from the Chapare region, Bolivia

Abstract: Overall morphological similarity and intrapopulation variation of morphological features make species identification in cryptic species complexes challenging. In such cases, additional features, such as acoustic and/or genetic characters, are being used to aid species identification. The use of acoustic signals as a suite of diagnostic features can be especially rewarding in certain taxonomic groups that rely on acoustic communication. Such is the case of the Neotropical leaf litter frogs of the Leptodactylus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 59 publications
(90 reference statements)
1
33
0
2
Order By: Relevance
“…However, some authors (Fouquet 2007, Angulo and Reichle 2008, Funk 2012 have suggested that undescribed cryptic diversity may increase this number markedly. Minimally 332 amphibian species occur in Amazonian Brazil; these include 309 salamanders (Brcko 2013, Hoogmoed 2016a, and 18 caecilians (Hoogmoed 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors (Fouquet 2007, Angulo and Reichle 2008, Funk 2012 have suggested that undescribed cryptic diversity may increase this number markedly. Minimally 332 amphibian species occur in Amazonian Brazil; these include 309 salamanders (Brcko 2013, Hoogmoed 2016a, and 18 caecilians (Hoogmoed 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Anuran vocalizations are critical for sexual Bee 2007, Wells 2007), which have made their descriptions an important taxonomic tool (e.g., Angulo and Reichle 2008, Glaw et al 2010, Martins and Giaretta 2011, Carvalho and Giaretta 2013. Therefore, describing the calls of the remaining species and comparing topotypical data among populations might be relevant for the taxonomy of species in the Hypsiboas polytaenius group.…”
Section: Introductionmentioning
confidence: 99%
“…Two species are considered widespread in the Amazon (L. andreae Müller, 1923 andL. hylaedactylus (Cope, 1868) but it is widely known that both represent complexes of species (ANGULO & REICHLE 2008, A. Angulo pers. comm.…”
Section: Threatsmentioning
confidence: 99%